Delayed Bilateral Chylothorax After Cholecystectomy Without Thoracic Intervention: A Rare Case Report - Çebi, Işıl; Yılmaz, Meltem (The European Research Journal, 2026)
Chylothorax is an uncommon cause of pleural effusion, most frequently associated with thoracic trauma, malignancy, or congenital lymphatic disorders. Development of chylothorax following abdominal surgery without direct thoracic intervention is rare. We report a 77-year-old female who developed delayed bilateral pleural effusions after cholecystectomy and was subsequently diagnosed with chylothorax. The clinical course was notable for an intervening enterocutaneous fistula. Diagnosis was confirmed by pleural fluid analysis demonstrating markedly elevated triglyceride levels. The patient was successfully managed with conservative treatment, including pleural drainage and total parenteral nutrition, without the need for surgical intervention. This case highlights a rare delayed presentation of chylothorax following abdominal surgery and underscores the importance of considering lymphatic complications in complex postoperative courses.